Nanocarrier-Based Approaches for the Efficient Delivery of Anti-Tubercular Drugs and Vaccines for Management of Tuberculosis - Rajput, Amarjitsing; Mandlik, Satish; Pokharkar, Varsha (Frontiers in Pharmacology, 2021)
Drug-resistant species of tuberculosis (TB), which spread faster than traditiona TB, is a severely infectious disease. The conventional drug therapy used in the management of tuberculosis has several challenges linked with adverse effects. Hence, nanotherapeutics served as an emerging technique to overcome problems associated with current treatment. Nanotherapeutics helps to overcome toxicity and poor solubility issues of several drugs used in the management of tuberculosis. Due to their diameter and surface chemistry, nanocarriers encapsulated with antimicrobial drugs are readily taken up by macrophages. Macrophages play a crucial role as they serve as target sites for active and passive targeting for nanocarriers. The surface of the nanocarriers is coated with ligand-specific receptors, which further enhances drug concentration locally and indicates the therapeutic potential of nanocarriers. This review highlights tuberculosis’s current facts, figures, challenges associated with conventional treatment, different nanocarrier-based systems, and its application in vaccine development.